Ultra-Long GnRH Agonist Protocol During IVF/ICSI Improves Pregnancy Outcomes in Women With Adenomyosis: A Retrospective Cohort Study - Lan, Jie; Wu, Yaoqiu; Wu, Zexuan; Wu, Yingchen; Yang, Rong; Liu, Ying; Lin, Haiyan; Jiao, Xuedan; Zhang, Qingxue (Frontiers in Endocrinology, 2021)
Objective: This study aimed to compare the ultra-long gonadotropin-releasing hormone agonist (GnRH-a) protocol and the long GnRH-a protocol during in vitro fertilization (IVF) or intracytoplasmic sperm (ICSI) treatment on fertility outcomes in women with adenomyosis. Materials and Methods: This study was a retrospective cohort study. From January 2011 to May 2018, a total of 371 fresh IVF/ICSI cycles were included. Among the cycles included, 237 cycles of 212 women underwent the ultra-long GnRH-a protocol, while 134 cycles of 116 women underwent the long GnRH-a protocol. The rates of implantation, clinical pregnancy per embryo transfer, live birth, and early miscarriage were estimated between the compared protocols. Results: In the study, the early miscarriage rate in women undergoing the ultra-long GnRH-a protocol was significantly lower than those undergoing the long GnRH-a protocol (12.0% versus 26.5%, p = 0.045). Whereas, the differences in the rates of biochemical pregnancy, implantation, clinical pregnancy, and live birth in women between the two groups showed no statistical significance. The pregnancy outcomes were also sub-analyzed according to the adenomyotic region (diffuse and focal). As for diffuse adenomyosis, the rates of clinical pregnancy and live birth in women undergoing the ultra-long GnRH-a protocol were significantly higher than those undergoing the long GnRH-a protocol (55.3% versus 37.9%, p = 0.025; 43.4% versus 25.9%, p = 0.019, respectively). But pregnancy outcomes showed no difference between the two protocols in women with focal adenomyosis. Conclusions: The ultra-long GnRH-a protocol during IVF/ICSI improves pregnancy outcomes in women with adenomyosis, especially in women with diffuse adenomyosis when compared with the long GnRH-a protocol.